PENDIDIKAN ISLAM DI ERA GLOBALISASI DAN MODERNISASI - Masrifah, Rofia; Usman, Syahruddin; Ondeng, Syarifuddin (Program Studi Pendidikan Teknologi Informasi Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
Islamic education is the education of the whole person, reason and skills with the aim of preparing people to live a better life. However, this does not go straight, because Islamic education is influenced by the current current of globalization. Globalization is a big threat to Islamic education. Changes in the field of education include educational content, educational methods, educational media, and so on. One aspect that has a huge influence is the curriculum. The research design used is the literature review method. Literature study (literature review) is research carried out by researchers by collecting a number of books, journals, articles, research results related to research problems and objectives. Based on the results of research on Islamic education in the era of globalization and modernization, the following can be concluded: Every human being has a desire for education. As a Muslim, education is absolutely necessary to achieve the goal of creating humans on earth as the Khalifah of Allah. With the development of technology and changes in human needs, nothing can escape these developments and changes, including the world of education, especially Islamic education.